Magneto-optical spectra of an organic antiferromagnet as a candidate for an altermagnet - Satoshi Iguchi; Hiroki Kobayashi; Yuka Ikemoto; Tetsuya Furukawa; Hirotake Itoh; Shinichiro Iwai; Taro Moriwaki; Takahiko Sasaki (Physical Review Research)
We have measured the magneto-optical Kerr effect (MOKE) in an orthorhombic organic antiferromagnet κ-(BEDT-TTF)_{2}Cu[N(CN)_{2}]Cl (κ-Cl), which is a candidate for an altermagnet. From the Maxwell equations, we derived matrix-type general formulae describing the optical propagation and reflection for arbitrary crystals. These formulae enabled us to correctly measure and obtain the off-diagonal optical responses of κ-Cl. The MOKE of κ-Cl appeared at around the Néel temperature and exhibited a nonlinear field dependence in the antiferromagnetic phase. This nonlinear field dependence eliminates a simple origin due to the net canted magnetization. The obtained off-diagonal optical conductivity spectra for the entire π-electron band clearly show three features. One is the large peaks at the spectral ends due to the magnetic origin with the large energy scale compared to the very small spin-orbit interaction in κ-Cl. The others are the middle region spectra proportional to the diagonal conductivities, possibly related to the symmetric piezomagnetic effect and the standard antisymmetric origins. These results suggest the altermagnetic response of κ-Cl. We also discuss the analogy between the magnetization in ferromagnets and the net magnetization and Néel vector with respect to the magneto-optical configurations.